BULGARIA’S TOBACCO INDUSTRY, LEGISLATION, AND POLITICS AFTER THE WORLD WAR I - Spasov Kitanov, Valentin (Revista Inclusiones, 2020)
Tobacco has been one of the most important production sectors in the economic life of Bulgarian lands and the Bulgarian state for centuries. A number of economic, legislative and political factors determine the historical development of tobacco production. After the restoration of the Bulgarian state in 1878, in just a few decades, the tobacco industry and the tobacco trade began to play a significant role in Bulgaria's economic, political and international life. The awareness of the significant role that tobacco production plays in the social and financial system of the country leads to the modern development of tobacco legislation in that time. The positive attitude of the state, the entrepreneurial spirit of private capital and the adequate changes in the legal framework enable the country to take advantage of the international changes in the historical period under discussion and to establish itself as one of the world leaders in the production and trade of Oriental tobacco.